Transmission risk and protective protocols for COVID-19 in dentistry: systematic review - Alshammary, Dr. Heba; Abumismar, Dr. Munther (International Journal of Dental Research, 2022)
Background: According to WHO, the new COVID-19 cases are rising with 4.5 million new cases in the first week of April 2021 and over 76000 new deaths globally. The risk of COVID-19 transmission in dental settings has been a concern. Therefore, this study aims to assess the transmission risk in dentistry and review the infection-control measures followed in different dental clinics worldwide and their compliance with the standard country-based or international guidelines.Methods: This study reviewed the published literature regarding the COVID-19 transmission-control guidelines followed by different dental care centers worldwide. We performed a comprehensive literature search in PubMed and Embase databases. The key guidelines were listed study-wise, divided into three parts: before entering the dental treatment, during the dental procedure, and after the dental procedure. A comparison study was conducted to assess the compliance with the country-based or internationally accepted recommendations given by WHO, ADA, CDC, etc., for dental practices in the COVID-19 pandemic.Results: During the dental procedure, a rubber dam and high volume saliva ejectors are recommended to minimize aerosol diffusion; mouth rinsing with 1% hydrogen peroxide or 0.2% povidone-iodine is recommended for patients. After the treatment, proper disinfection of the surfaces and instruments must be followed; the reusable dental instruments should be sterilized. Different guidelines were followed in different dental settings depended on the geographical locations; however, the most commonly followed guidelines were provided by WHO, ADA, CDC, and NHS.Conclusions: The available guidelines will contribute to the prevention of COVID-19 in dental settings. Although the dental clinics are adopting standard guidelines to prevent COVID-19 transmission, the joint efforts and cooperation of both patients and dental practitioners are needed to make it successful. Therefore, both parties should strictly adhere to their respective recommended guidelines and hand hygiene practice in dental settings.